PERAN ORANG TUA TERHADAP PENERAPAN PROTOKOL KESEHATAN SISWA SMP IT AL-MADINAH PADA PEMBELAJARAN TATAP MUKA TERBATAS DI MASA PANDEMI - Anggia Nur 'Ardhia Safitri (2022)
On March 2, 2020, Indonesia reported a COVID-19 case. The Department of Education will allow for limited face-to-face learning in 2022 as long as health protocols are followed. In this regard, health protocols for school students who are aided by parents as the primary role in the nuclear family must be implemented. The goal of this study is to determine the role of parents in the implementation of health protocols for SMP IT Al-Madinah students in limited face-to-face learning during the pandemic. As many as 163 students were used as samples. This information was gathered by distributing questionnaires in the form of a Google form containing a questionnaire on the role of parents and the application of health protocols. The data analysis used is a univariate and bivariate analysis using Chi-Square. The Chi-Square test results (p-value = 0.003) indicate that the role of parents plays a role in the application of the student's health protocol. The study's conclusion is the role of parents in the implementation of health protocols for SMP IT Al-Madinah students in limited face-to-face learning during the pandemic. According to the researchers, students should always follow health protocols at school, and parents should always teach and remind their children to follow health protocols.